Pecos Bill : a tall tale - Kellogg, Steven (New York : Morrow, 1986)
Incidents from the life of Pecos Bill, from his childhood among the coyotes to his unusual wedding day.
Keywords: Pecos Bill -- (Fictitious character) -- Legends; Folklore -- United States; Tall tales